2021
DOI: 10.5817/cp2021-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexting during social isolation: Predicting sexting-related privacy management during the COVID-19 pandemic

Abstract: During the global COVID-19 pandemic, many people were physically separated from their romantic or sexual partners and added sexting to their sexual repertoire. Sexting involves the exchange of sensitive data and thus necessitates personal and interpersonal privacy management strategies such as information control and privacy boundary communication. This study investigates the psychological predictors of sexting-related privacy management. In an online survey with 494 young adults, we tested demographic, psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…As digital sexuality and dating become more prevalent (Banerjee & Sathyanarayana, 2021;Courtice & Shaughnessy, 2017;Fisico, 2021;Lehmiller et al, 2021;Nessaibia et al, 2021;Thomas et al, 2021;Maes & Vandenbosch, 2022), the findings of the present study inform the impressions made by potential romantic partners through the exchange of explicit media. While most research has prioritized the face pictures and biographies of potential partners (Anzani et al, 2018;Dai & Robbins, 2021;Ramaker, 2020), the present finding take a step forward to investigate how pictures of penises may contribute to the holistic perception of the person within digital spaces.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As digital sexuality and dating become more prevalent (Banerjee & Sathyanarayana, 2021;Courtice & Shaughnessy, 2017;Fisico, 2021;Lehmiller et al, 2021;Nessaibia et al, 2021;Thomas et al, 2021;Maes & Vandenbosch, 2022), the findings of the present study inform the impressions made by potential romantic partners through the exchange of explicit media. While most research has prioritized the face pictures and biographies of potential partners (Anzani et al, 2018;Dai & Robbins, 2021;Ramaker, 2020), the present finding take a step forward to investigate how pictures of penises may contribute to the holistic perception of the person within digital spaces.…”
Section: Discussionsupporting
confidence: 60%
“…As definitions of what constitutes sexual behavior becomes more ambiguous, the authors highlight the growing concerns of digital infidelity. Past research of sexting behaviors have primarily focused on the negative outcomes associated with them, as concerns about privacy and exploitation abound in digital spaces (Fisico, 2021 ; Maes & Vandenbosch, 2022 ; Thomas et al, 2021 ). Additionally, Lehmiller et al ( 2021 ) argued that while they observed digital sexuality behaviors increased, it was not associated with overall well-being or satisfaction during COVID-19 lockdowns.…”
Section: Digitized Sexualitymentioning
confidence: 99%
“…Así, la desinhibición de las dos revoluciones, pueden llevar al individuo a cruzar un umbral de riesgo altamente peligroso (Agustina y Gómez-Durán, 2016). Thomas et al (2021) señalan dos estrategias empleadas por los adultos a la hora de realizar sexting: el intercambio de contenido sexual, insinuante o provocativo entre personas conocidas en entornos offline y no mostrar la cara en el ciberespacio.…”
Section: Discussionunclassified
“…Behavior & Law Journal,7(1),[35][36][37][38][39][40][41][42] práctica, la gestión de la privacidad del contenido público en entornos cibernéticos también se relaciona con la edad. Así, Thomas et al (2021) indican que "aunque los adultos se preocupan más por la privacidad a medida que envejecen, en las redes sociales, los adultos mayores utilizan menos estrategias de gestión de la privacidad que los adultos más jóvenes" (p. 8).…”
Section: B Factores De Riesgo Relacionados Con El Sextingunclassified
“…Sexting as a type of online threat has been addressed by several researchers in Slovakia and abroad. In Slovakia in particular Slovakia (Hollá, 2013;Hollá, et.al Thomas et al, 2021) and many others. Sexting is a medium that provides external validation and desirable or undesirable feelings for young vulnerable people.…”
Section: Introductionmentioning
confidence: 99%